Encouraging a driving safety culture through positive peer pressure with courtesy - Guillaume Alinier (6952004) (2015)
Although road safety and driver behaviour have improved over the last few years in Qatar, more accidents can be prevented and still more lives saved. One simple and very important step to reduce the severity of injuries for drivers and passengers is the proper and consistent use of a seat belt (1). Since law enforcement is not always effective, additional approaches should be used. We believe a road safety culture needs to be developed amongst drivers to further reduce road fatalities worldwide (2,3). If something potentially unsafe is noticed (dysfunctional break light, low tire pressure, unsecured passengers,…) something needs to be done to correct the situation and prevent potential harm. Thinking “It is not my problem!” implies allowing that person or family to potentially suffer severe consequences relating to an oversight on their part. The approach which has been piloted by both authors consists of the following: - Stationary in the traffic near a vehicle linked with a safety breach. - Make a gentle hand wave in a welcome manner to the driver or passenger. - Open your window to amicably mention the issue or point it by for example showing your seat belt. - Upon resolution of the situation greet the person with a thumb up and a smile. The experience has been positive at an estimated 95% rate, resulting in the return of a smile, the readjustment of the unsafe situation, and even many “Thank you”. Road safety is everyone’s responsibility. Peer pressure can influence behaviour in either way depending on what is promoted (4). Such simple approach can encourage a cultural shift promoting driving safety if spread. Stickers with clear messages that can be pointed to on side windows can help communicating without opening windows and hence diminish the feeling of intimidation. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.18